2012
DOI: 10.1021/es300556m
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Nuclear Accident: Fission and Activation Product Releases from the Fukushima Daiichi Nuclear Facility as Remote Indicators of Source Identification, Extent of Release, and State of Damaged Spent Nuclear Fuel

Abstract: This document was printed on recycled paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…Local food supply in farming areas did not necessarily increase exposure to radiocesium because local municipalities routinely screen food products for personal consumption. Release of 90 Sr and other less volatile radionuclides from the FDNPP meltdown was considered to be limited compared with that of 137 Cs (34). A survey showed that the concentration of 90 Sr in soil samples was quite low (ca.…”
Section: Discussionmentioning
confidence: 99%
“…Local food supply in farming areas did not necessarily increase exposure to radiocesium because local municipalities routinely screen food products for personal consumption. Release of 90 Sr and other less volatile radionuclides from the FDNPP meltdown was considered to be limited compared with that of 137 Cs (34). A survey showed that the concentration of 90 Sr in soil samples was quite low (ca.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of the radioactive plume and its deposition over the Pacific Ocean (Aoyama et al 2013;Honda et al 2012), North America (e.g., Schwantes et al 2012;Zhang et al 2011), and Europe (e.g., Masson et al 2011) as well as within the Japanese Cs deposition level using a trinomial exponential function. The present simple estimation shows that more than a decade would be necessary for the 137 Cs atmospheric deposition level to return to pre-accident levels territories (Hirose 2012;Kinoshita et al 2011;Morino et al 2011;Terada et al 2012;Tsuruta et al 2014) has been well depicted by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its chemical similarity to calcium, 90 Sr is accumulated in the bone and may cause leukemia or skeletal cancer. Its presence in the environment, therefore, causes much concern as it is often dictating risk of contaminated sites over longer periods of time and calls for the monitoring of this inconvenient radionuclide [18]. This is of great importance especially for ensuring food safety.…”
Section: Introductionmentioning
confidence: 99%